From Adventure to Therapy: A Model for Healing - Lee, Ken Kok Wai (INTI Publishing House Sdn Bhd, 2005)
Adventure therapy (AT) uses outdoor modalities that immerse clients in natural environments and challenging outdoor experiences to improve psychological dysfunctions in emotion, behavior, and life effectiveness skills. The healing power of AT rests on the therapeutic factors of the natural world, the role of the treatment team and the effective and intentional use of adventure therapy tools. The AT practitioner ¡s both a competent adventurer and professional helper who helps clients begin their process of personal change. The effects of AT are growth-producing and will take them on a journey that lasts a lifetime. It also reduces the reference to the stigma clients assign to traditional forms of therapy. AT interventions tend to be solution- focused and humanistic in their orientation, although many programmes also have important behavioral underpinnings, particularly for programmes involving delinquent youths, conduct disorder, low self-esteem, oppositional defiance, adjustment disorder, bipolarity, grief, chemical dependency and dysfunctional families. AT has been purported to be a potentially unique therapeutic modality that can be used either independently or as an adjunct to other forms of psychotherapy. AT programmes perceive clients with innate goodness and having the resources needed for change. They can be guided to know where and how to access them to make the desired change. This paper also examines the way and the conditions under which adventure activities can become therapeutic. It determines change as a central concept in the therapeutic process. The foundations of adventure therapy, its rationale and strategies, and therapeutic factors are discussed. In addition, it illustrates a local case of AT in practice and introduces the potential use of AT in the Programme Khidmat Negara (PKN) (National Service Programme) in Malaysia. This paper includes some timely recommendations in working with youths who are on the PKN programme in order to deal with problem behaviors and to obtain long lasting change.